An approach for utilization of direct coal liquefaction residue: Blending with low-rank coal to prepare slurries for gasification. (1st April 2015) - Lv, Dongmei; Yuchi, Wei; Bai, Zongqing; Bai, Jin; Kong, Lingxue; Guo, Zhenxing; Yan, Jingchong; Li, Wen
Highlights: The liquefaction residue can improve the slurryability of low-rank coals. YM and SM coal have synergistic effect with the residue in slurryability. Blending slurries with the residue and low-rank coal have strong pseudoplasticity. Static stability of blending slurries is remarkable. Abstract: Direct coal liquefaction residue (DCLR) is a main byproduct in direct coal liquefaction process and its clean and high-efficient utilization is important. If DCLR could be gasified for hydrogen production, it will compensate hydrogen consumption during liquefaction and lower the operation cost, which makes DCLR utilization more promising. We proposed to blend DCLR with low-rank coals to prepare DCLR–coal–water slurries (DCLRCWS) as feedstock for gasification. In this work, one DCLR and four low-rank coals were used to prepare the individual DCLR–water slurries (DCLRWS), coal water slurries (CWS) and the mixed DCLRCWS at the weight ratio of 1:1. The slurryability, static stability and rheology of various slurries were investigated. The results show that DCLR and the low-rank coals are complementary in terms of slurry properties and DCLRCWS could meet the requirement of gasification process. Adding 50 wt.% DCLR apparently improves the slurryability of low-rank coals, and the maximum solid loading ( C max ) of DCLRCWS prepared with ZLNR coal and DCLR is about 10% higher than that of the corresponding CWS. The effects of coal properties, dispersant adsorption, zeta potential on preparation of highly loaded slurries were examined in terms of slurryability. Moreover, compared with DCLRWS, DCLRCWS display higher degree of pseudoplasticity and better static stability owing to the addition of low-rank coals.